Phase II trial of sorafenib in advanced salivary adenoid cystic carcinoma of the head and neck. Issue 2 (13th March 2014) - Thomson, David J.; Silva, Priyamal; Denton, Kim; Bonington, Suzanne; Mak, Soo K.; Swindell, Ric; Homer, Jarrod; Sykes, Andrew J.; Lee, Lip W.; Yap, Beng K.; Slevin, Nicholas J.
Abstract Background There is a need to improve the systemic treatment of advanced adenoid cystic carcinoma (ACC). Response rates to chemotherapy are poor and preliminary investigations of molecularly targeted agents have been disappointing. In this study, we evaluate sorafenib, an oral multikinase inhibitor, which has an attractive targeting profile for this disease. Methods In a single‐arm phase II trial, patients with unresectable locally recurrent and/or metastatic ACC were treated with sorafenib 400 mg bid. Results Twenty‐three patients, median age 51 years, were recruited from 2009 to 2011. Median progression‐free survival (PFS) and overall survival (OS) were 11.3 and 19.6 months, respectively. PFS at 6 and 12 months were 69.3% and 46.2%, respectively. Sorafenib was only reasonably well tolerated, and 13 patients (57%) experienced grade 3 toxicity. Conclusion Sorafenib showed modest activity in ACC with a 12‐month PFS of 46.2%. Sorafenib 400 mg bid was associated with significant toxicity and, taken together with limited effectiveness, cannot be enthusiastically recommended for further evaluation. © 2014 Wiley Periodicals, Inc. Head Neck37: 182‐187, 2015